Add-On Selective Estrogen Receptor Modulators for Methadone Maintenance Treatment - Huang, Chieh-Liang; Chiang, Yao-Chang; Chang, Wei-Chun; Su, Yu-Ting; Yang, Juan-Cheng; Cheng, Wei-Chung; Lane, Hsien-Yuan; Ho, Ing-Kang; Ma, Wen-Lung (Frontiers in Endocrinology, 2021)
Methadone maintenance treatment (MMT) remains the cornerstone for the management of opiate abuse. However, MMT can be associated with complex factors, including complications during the tolerance phase, the inability of some patients to maintain treatment effects during the tapering or abstinence phases, and the development of methadone dependence. Previous studies have revealed a sex disparity in MMT efficacy, showing that women undergoing MMT experiencing an increase in psychological symptoms compared with men and suggesting a link between disparate responses and the effects of estrogen signaling on methadone metabolism. More specifically, estradiol levels are positively associated with MMT dosing, and the expression of a single-nucleotide polymorphism (SNP) associated with estrogen receptor (ER) regulation is also associated with MMT dosing. In addition to performing mechanistic dissections of estrogen signaling ablating the effect of methadone, past studies have also proposed the targeting of estrogen signaling during MMT. The present report provides an overview of the relevant literature regarding sex effects, including differences in sex hormones and their potential impacts on MMT regimens. Moreover, this article provides a pharmacological perspective on the targeting of estrogen signals through the use of selective ER modulators (SERMs) during MMT. Preliminary preclinical experiments were also performed to evaluate the potential effects of targeting estrogen signaling with tamoxifen on methadone metabolism.